Physical Education Teachers’ Strategies and Challenges in Instructional Delivery in the Post Pandemic Era - Culajara, Carla Jobelle (International Journal of Social Learning (IJSL), 2024)
The study explores the physical education teachers’ strategies and challenges in instructional delivery in the post-pandemic era. The study used qualitative research design using phenomenological approaches. Ten physical education teachers participated in the survey to share their experiences delivering instructions in the post-pandemic era. Codes and themes were transcribed in the study. Based on the study, the following themes have emerged:  technology-based instructions, differentiated teaching strategies, socio-emotional preparedness, and engagement of students. Based on the findings, as part of the change, teachers are expected to develop their instructional practices further and keep up with the trend of delivering quality education services. As teachers improve and enhance their practices in providing instructions, they experience challenges that serve as an avenue of learning and upskilling their strategies as well as their mechanisms of teaching in the post-pandemic era. Thus, integrating technology and upskilling the knowledge and skills in instructional delivery must be prioritized in the ever-changing educational landscape.